2017
DOI: 10.1111/jvp.12464
|View full text |Cite
|
Sign up to set email alerts
|

Phenylbutazone induces equine glandular gastric disease without decreasing prostaglandin E2concentrations

Abstract: In equids, phenylbutazone at high doses induces gastric disease, primarily in the glandular portion of the stomach. However, the mechanism of nonsteroidal anti-inflammatory drug (NSAID)-induced gastric disease in horses has yet to be determined. While phenylbutazone-associated ulceration is often attributed to a decrease in basal gastric prostaglandins, this has not been demonstrated in the horse. Twelve horses were randomly assigned to treatment (n = 6; 4.4 mg/kg phenylbutazone PO in 20 ml molasses q 12 hr fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
4
21
0
1
Order By: Relevance
“…Prostaglandins are considered a critical part of the mucosal barrier, contributing to mucous secretion, blood flow, bicarbonate secretion, and inhibition of acid secretion 23. However, in two studies using an experimental (nonsteroidal anti-inflammatory drug-induced) model of EGGD, glandular mucosal prostaglandins (PGE and/or PGI) did not decrease following treatment with 1–7 days of phenylbutazone 24,25. Furthermore, there was no association between NSAID use and glandular ulcers in racehorses in training 14.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Prostaglandins are considered a critical part of the mucosal barrier, contributing to mucous secretion, blood flow, bicarbonate secretion, and inhibition of acid secretion 23. However, in two studies using an experimental (nonsteroidal anti-inflammatory drug-induced) model of EGGD, glandular mucosal prostaglandins (PGE and/or PGI) did not decrease following treatment with 1–7 days of phenylbutazone 24,25. Furthermore, there was no association between NSAID use and glandular ulcers in racehorses in training 14.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Phenylbutazone, a non‐selective inhibitor of cyclo‐oxygenase (cyclo‐oxygenase‐1, COX‐1; and cyclo‐oxygenase 2, COX‐2), is the most commonly prescribed NSAID for equine orthopaedic pain in the US 1 . Adverse effects of non‐selective COX inhibitors (such as phenylbutazone) in horses include renal medullary necrosis and ulceration of the gastrointestinal tract, primarily the glandular gastric mucosa and right dorsal colon 2‐9 …”
Section: Introductionmentioning
confidence: 99%
“…However, prostaglandins appear to play a lesser role in NSAID‐induced enteropathy 11,12 . In horses, decreases in neither glandular gastric nor colonic prostaglandin concentration (PGE ± PGI) were observed despite induction of glandular ulceration or clinical (hypoalbuminemia and neutropenia) or pathological findings consistent with right dorsal colitis 4,13‐15 . Other mechanisms contributing to GI damage include increased reactive oxygen species formation through mitochondrial uncoupling, decreased hydrophobicity of the mucosa and topical irritation from luminal factors, including acid (stomach) or bile (intestine) and bacteria 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it is quite clear that high doses of NSAIDs can cause EGGD, the potential of NSAIDs to cause EGGD under a clinical dose regimen is unclear. Andrew et al [3] reported that a clinical dose of phenylbutazone (approximately 2.6 mg/kg/day) did not induce gastric ulceration when administered for 2 weeks whereas Pedersen et al [32] used a higher recommended dose (4.4 mg/kg twice a day) for a week and caused EGGD in all horses.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ESGD, EGGD appears to be an emerging disease (specifically in sport horses) about with little is known and that has had limited research. The possible risk factors for EGGD include breed, management, stress [29], and non-steroid anti-inflammatory drugs (NSAIDs) [32]. It is believed that NSAIDs can induce gastric damage by inhibition of COX enzymes leading to decreased concentration of mucosal prostaglandins (PGs), which play an important role in gastric mucosa protection [20, 28].…”
mentioning
confidence: 99%